(untitled) (Perner’s Contacts, 2023)
In recent years, the field of railway traffic management has been receiving increasing interest from the professional public. This is evidenced not only by professional publications from past years, but also by the increased interest in information regarding the nature of the methods of remote control of railway traffic through the Central Dispatch Offices. The aim of this contribution is to provide an overview of selected scientific publications in this area over the last few years. For this purpose, articles from the Web of Science (WoS) from 2020 to 2023 were used.